Collaborative music-making: special educational needs school assistants as facilitators in performances with accessible digital musical instruments - Lindetorp, Hans; Svahn, Maria; Hölling, Josefine; Falkenberg, Kjetil; Frid, Emma (Frontiers in Computer Science, 2023)
The field of research dedicated to Accessible Digital Musical Instruments (ADMIs) is growing and there is an increased interest in promoting diversity and inclusion in music-making. We have designed a novel system built into previously tested ADMIs that aims at involving assistants, students with Profound and Multiple Learning Disabilities (PMLD), and a professional musician in playing music together. In order to identify drivers and barriers for the assistants to take part in such activities, we have performed a workshop and evaluated the setup using quantitative as well as qualitative methods. One of the main findings was that the sounds from the ADMIs added to the musical context without making errors that impacted the music negatively even when the assistants mentioned experiencing a split between attending to different tasks, and a feeling of insecurity towards their musical contribution. Our study highlights how a system of networked and synchronized ADMIs could be conceptualized to include assistants more actively in collaborative music-making, as well as design considerations that support them as facilitators.